A time-independent kinetic model for syngas production from oxy-fuel gasification of waste oil. Issue 11 (3rd June 2017) - Gao, W.; Farahini, M. R.; Rezaei, M.; Foruzanfar, Z.; Jamil, M. K.; Imran, M.; Baig, A. Q.
ABSTRACT: Clean heat and power generation for industrial applications is a major challenge in the recent decade. Gasification is a clean thermochemical process to produce syngas through partial oxidation. In this paper, we develop an unsteady state kinetic model of gasification to produce syngas from petroleum residue and also evaluate the tar and char yield in the oxy-fuel conditions. Results showed that the oxy-fuel gasification can be used to produce high caloric value syngas with low emissions and costs. It is also found that the system pressure reduces the hydrogen yield, although it is not considerable. Modeling results validated against the experimental data and found to be in a good agreement.